Minimization of Socio-Economic Impacts During Mine Closure - Miradouro, L; Piagentini, SM; Costa, MRSM (Mine Closure 2008: Third International Seminar on Mine Closure, 2008)
Votorantim Group, one of the largest Brazilian conglomerates, was founded 90 years ago, and has since been committed to productive investments, sustainable growth, and social responsibility. It operates in eight different business areas, with metals accounting for more than 30% of the group’s income. The closure of their industrial unit’s nickel mine situated in Fortaleza de Minas, MG, Brazil is scheduled to take place in 2010. The group has been addressing this issue since 2003, through a project aiming at socio- economic development and income generation in the city, where the industrial unit is located, in order to cope with the environmental aspects involved and stakeholders’ socio-economic expectations. The challenge consists of mitigating the socio-economic impact of a tax-collection reduction of 30% on potential unemployment growth. The project, An Eye in the Future, was designed in order to provide the implementation of a sustainable model for Fortaleza de Minas local development, capable of leading to economic prosperity, environmental quality of the ecosystem, and strengthening the community. The project is based on the premise of systemic thinking, and adopts the following methodological tools: interconnectivity or interdependence, respect for diversity, sharing, co-responsibility, recycling or energy and resources exchange, and flexibility. The scientific rationality added to the subjectivity (basis of the systemic thinking) favors the achievement of the projected results, such as standards and paradigms shift, solutions for intrapersonal and interpersonal conflicts, personal and collective transformation and the construction of a new development model.